Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-02-09T18:12:18+01:00
Salut,
a.
4(x+5) = 10x + 3 \\
4x + 20 = 10x + 3 \\
4x - 10x = 3 -20 \\
-6x = -17 \\
x =   \frac{-17}{-6} =  \frac{17}{6}
b.
3(x-2) = 6(x+4) \\
3x - 6 = 6x + 24 \\
3x - 6x = 24 + 6 \\
-3x = 30 \\
x =  \frac{30}{-3} = -10
c.
7x - (5x + 3 ) = 5(x-3) + 2 \\
7x - 5x - 3 = 5x - 15 + 2 \\
-2x - 3 = 5x - 13 \\
-2x - 5x = -13 + 3 \\
-7x = -10 \\
x =  \frac{-10}{-7} =  \frac{10}{7}
d.
7(n+2) - 3 = 25 - (3n+4) \\
7n + 14 - 3 = 25 - 3n - 4 \\
7n + 11 = 21 - 3n \\
7n + 3n = 21 - 11 \\
10n = 10 \\
n =  \frac{10}{10} = 1
e.
4y + 3(4y -2) = 3(y+1) \\
4y + 12y - 6 = 3y + 3 \\
16y - 6 = 3y + 3 \\
16y - 3y = 3 + 6 \\
13y = 9\\
y =  \frac{9}{13}

Bonne journée!
Attention, erreur !
c. 7x - 5x = 2x . A la fin tu as donc -3x = -10. donc x = 10/3
Merci beaucoup!
2014-02-09T18:14:31+01:00
A. 4x + 20 = 10x +3 
20-3 =10x-4x
17 = 6x
6x=17
x=17/6

b. 3x - 6 = 6x + 24 
3x - 6x = 24+6
-3x =30
x= -10

c. 7x - (5x+3)=5(x-3)+2
7x - 5x - 3 = 5x - 15 + 2
2x - 3 = 5x - 13
2x - 5x = - 13 + 3
-3x = -10
x = 10/3

d. 7( n + 2 ) - 3 = 25 - ( 3n + 4 )
7n + 14 - 3 = 25 - 3n - 4 
7n + 11 = - 3n + 21
7n + 3n = 21 - 11
10n = 10
n = 1

e. 4y + 3(4y - 2) = 3(y +1) 
4y + 12y - 6 = 3y + 3 
16y - 6 = 3y + 3 
16y - 3y = 3+6
13y = 9
y = 9/13